Neuroimaging dual task performance in youth after sports-related concussion: an fMRI study. Issue 5 (11th March 2013) - Keightley, Michelle L; Sinopoli, Katia; Wells, Greg; Chen, Jen-Kai; Taha, Tim; Ptito, Alain
Abstract : Objective: To identify the neural substrates of a dual-task paradigm and evaluate performance in concussed versus non-concussed youth 3–6 months post-injury. Design: Standard structural (T1, T2, FLAIR, DTI) and functional (single-shot T2 *-weighted pulse sequence with in-out spiral readout images) were collected using a 3 Tesla imaging system. fMRIstat was used to analyse the data. Setting: Male participants 9–15 years of age were recruited from The Greater Toronto Hockey League and The Hospital for Sick Children via poster advertising. Subjects: 13 concussed youth (mean age=12.61+1.55 years) and 14 control subjects (mean age 12.59±1.55 years). Intervention: None. Outcome Measures: Accuracy (ACC) and reaction time (RT) during (1) a 0–3 back visuospatial working memory task; (2) a two finger button pressing motor task and (3) dual-task cost associated with simultaneously performing the working memory and motor tasks. Results: There were no significant group differences across single and dual-task conditions. Although both groups activated similar brain regions across tasks, concussed youth demonstrated significantly less percent BOLD change in the prefrontal cortex across all working memory task comparisons. Similar results were found during the 1 vs 0 back and 2 vs 0 back dual task conditions, but not for the 3 vs 0 back dual task condition. Conclusions: Differences in brain function can be observed in youth who have sustained a single injury 3–6 months earlier. Further research is needed to identify the clinical correlates of these atypical activation patterns. Acknowledgements: Canadian Institute of Health Research (CIHR) and Ontario Neurotrauma Foundation (ONF). Competing interests: None.